Prevalence of Diabetes, Hypertension, and Associated of Cardiovascular Diseases: A Comparative Pre- and Post-COVID Study - Manuela Chiavarini; Jacopo Dolcini; Giorgio Firmani; Elisa Ponzio; Pamela Barbadoro (Diseases)
Background: Diabetes and hypertension are major global health challenges aggravated by COVID-19’s impact on healthcare and lifestyle factors. This study aims to compare the prevalence and associated socio-demographic factors of these conditions before and after the pandemic (2019 vs. 2022). Materials and Methods: We used data from Italy’s “Aspects of Daily Life” survey; 74,294 adults were included. Results: Results show a rise in diabetes prevalence from 7.76% in 2019 to 8.49% in 2022 (p < 0.05), while hypertension did not show this. Logistic regression analysis for the years 2019 and 2022 revealed a statistically significant association between the year 2022 and increased odds of diabetes (OR = 1.08, p = 0.008). BMI’s role as a risk factor intensified, with higher odds ratios (ORs) for both conditions in overweight and obese individuals in 2022. For example, obesity-related ORs for diabetes increased from 2.45 (95%CI 1.73–3.47) in 2019 to 3.02 (95%CI 2.09–4.35) in 2022, and for hypertension from 2.86 (95%CI 2.28–3.58) to 3.64 (95%CI 2.87–4.61). Lower education levels also showed a greater association with hypertension risk in 2022; subjects with only middle or high school diplomas had significantly higher ORs than individuals with higher education; there was a non-significant trend in 2019. However, diabetes risk associated with lower education remained stable and significant in both years. Conclusions: These findings suggest that the pandemic may have increased risk factors for diabetes and hypertension, particularly BMI and educational level, compared with the literature on the increased burden of chronic diseases during COVID-19.